LPS activates neuroinflammatory pathways to induce depression in Parkinson’s disease-like condition - Zhang, Jing; Xue, Bing; Jing, Bin; Tian, Huiling; Zhang, Naiwen; Li, Mengyuan; Lu, Lihua; Chen, Lin; Diao, Huaqiong; Chen, Yufei; Wang, Min; Li, Xiaoli (Frontiers in Pharmacology, 2022)
Aim: This study aimed to observe the effects of lipopolysaccharide (LPS) intraperitoneal (i.p.) injection on rats and investigate how neuroinflammation contributes to the pathogenesis of depression in Parkinson's disease (dPD). Methods: Rats were administered LPS (0.5 mg/kg, i.p.) for either 1, 2, or 4 consecutive days to establish a rat model of dPD. The sucrose preference test (SPT), the open field test (OFT), and the rotarod test evaluated depression-like and motor behaviors. Magnetic resonance imaging was used to detect alterations in the intrinsic activity and the integrity of white matter fibers in the brain. The expression of c-Fos, ionized calcium-binding adapter molecule (Iba-1), and tyrosine hydroxylase (TH) was evaluated using immunohistochemistry. The concentration of interleukin-6 (IL-6), tumor necrosis factor (TNF-α), and interleukin-10 (IL-10) was measured using Luminex technology. Results: LPS i.p. injections decreased sucrose preference in the SPT, horizontal and center distance in the OFT, and standing time in the rotarod test. The intrinsic activities in the hippocampus (HIP) were significantly reduced in the LPS-4 d group. The integrity of white matter fibers was greatly destroyed within 4 days of LPS treatment. The expression of c-Fos and Iba-1 in the prefrontal cortex, HIP, and substantia nigra increased dramatically, and the number of TH+ neurons in the substantia nigra decreased considerably after LPS injection. The levels of IL-6, TNF-α, and IL-10 were higher in the LPS-4 d group than those in the control group. Conclusion: Injection of LPS (0.5 mg/kg, i.p.) for 4 consecutive days can activate microglia, cause the release of inflammatory cytokines, reduce intrinsic activities in the HIP, destroy the integrity of white matter fibers, induce anhedonia and behavioral despair, and finally lead to dPD. This study proved that LPS injection (0.5 mg/kg, i.p.) for 4 consecutive days could be used to successfully create a rat model of dPD.